APPLICATION OF THE INTERNATIONAL CLASSIFICATION OF FUNCTIONING IN DISABLED PEOPLE DUE TO CORONARY ARTERY DISEASE - Komarida, О.О.; Kyrychenko, А.G.; Kornatskyi, V.М.; Sanina, N.А.; Tomakh, N.V.; Khanyukova, І.Y. (World of Medicine and Biology, 2023)
The article describes the possibilities of using the International Classification of Functioning, Disability and Health in the medical and social expertise of patients with coronary artery disease. From the new points of view were presented the limitations of functioning in terms of functions, structures, activity, and participation. A short set of domains was selected that characterize the functioning profile in patients with coronary artery disease. We developed a method for quantifying the severity of structural and functional disorders, limiting activity and opportunities for participation, and the degree of positive and negative impact of contextual factors that provides a single language for health and related indicators. The introduction of the International Classification of Functioning into the practice of medical and social expertise will allow a full transition to the biopsychosocial model of disability, will promote the objectification of both the process of medical and social expertise and rehabilitation of disabled people.
Keywords: international classification of functioning; medical and social expertise; disability; coronary artery disease